Co-Regulated Expression of TGF-? Variants and miR-21 In Bladder Cancer - Monfared, Hamideh; Ziaee, Seyed Amir Mohsen; Hashemitabar, Mahmoud; Khayatzadeh, Hamid; Kheyrollahi, Vahid; Tavallaei, Mahmood; Mowla, Seyed Javad (Urology Journal, 2013)
Purpose: To investigate a potential alteration in the expression levels of transforming growth factor β (TGF-β) and miR-21 in bladder cancer tissues. Material and Methods: Using real-time polymerase chain reaction (PCR) method, we examined a potential correlated expression of miR-21 and TGF-β variants in 30 bladder tumors and their marginal/non-tumor biopsy specimens obtained from the same patients. Results: Our data revealed a significant down-regulation of TGF-β variants (P = .03) along with a non-significant alteration in the expression of miR-21 in tumor vs. non-tumor samples. However, in contrast to low-grade tumors, the expression of miR-21 was upregulated in high-grade ones, and the expression level can efficiently discriminate low-grade tumors from high-grade ones (P = .03). Conclusion: In accordance to the observed similarity between TGF-β variants and miR-21 gene expression alterations in bladder tumors, treating 5637 bladder cancer cell line with TGF-β recombinant protein caused a significant upregulation of miR-21. The later finding further confirmed a correlated expression of TGF-β and miR-21 in bladder tumors.